Conformational analysis: A new approach by means of chemometrics - Bruni, A. T.; Leite, VBP; Ferreira, MMC (Wiley-Blackwell, 2002)
In conformational analysis, the systematic search method completely maps the space but suffers from the combinatorial explosion problem because the number of conformations increases exponentially with the number of free rotation angles. This study introduces a new methodology of conformational analysis that controls the combinatorial explosion. It is based on a dimensional reduction of the system through the use of principal component analysis. The results are exactly the same as those obtained for the complete search but, in this case, the number of conformations increases only quadratically with the number of free rotation angles. The method is applied to a series of three drugs: omeprazole. pantoprazole, lansoprazole-benzimidazoles that suppress gastric-acid secretion by means of H(+), K(+)-ATPase enzyme inhibition. (C) 2002 John Wiley Sons. Inc.
Keywords: principal component analysis; chemometrics; omeprazole; pantoprazole; lansoprazole; conformational analysis